Short Notices. - Minehan, Bridie Andrews; Whiteside, Noel; Steinbach, Susie L.; Rothman, E. Natalie; Murray, James M. (Social History, 2010)
The article reviews several books including "Prisoners of Want: The Experience and Protest of the Unemployed in France, 1921-1945," by Matt Perry, "Living in Sin: Cohabiting As Husband and Wife in Nineteenth-Century England," by Ginger S. Frost, and "Men of Empire: Power and Negotiation in Venice's Maritime State," by Monique O'Connell.